Urachal Cyst, a Rare Cyst with Multiple Complications - Amr Hawary; Peter Duffy (The Scientific World Journal)
Urachal cysts are rare, can be one of the forgotten causes of abdominal pain, and can present as adenocarcinoma of the bladder, along with many other presentations. There is a real need for physicians, general surgeons, and urologists to be acquainted with the different presentations and management of this rare condition.